Product differentiation and welfare in a mixed duopoly with regulated prices: the case of a public and a private hospital - Annika Herr (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Wirtschaftspolitik und Quantitative Wirtschaftsforschung (IWQW), 2009)
Hospital markets are often characterised by price regulation and the existence of different ownership types. Using a Hotelling framework, this paper analyses the effect of different objectives of the hospitals on quality, profits, and overall welfare in a price regulated duopoly with symmetric locations. In contrast to other studies on mixed oligopolies, this paper shows that in a duopoly with regulated prices privatisation of the public hospital may increase overall welfare depending on the difference of the hospitals' marginal costs and the weight of the additional public hospital's motive.
Keywords: L13; I18; H42; 330; mixed oligopoly; price regulation; quality; hospital competition; Krankenhaus; Produktdifferenzierung; Duopol; Oligopol; Staatliche Preispolitik; Wohlfahrtseffekt; Privatisierung; Wettbewerb; Theorie